(untitled) (مجلة إحالات, 2026)
The spread of what the West has taken from Arabs in the field of experimental science has covered what has been taken from literature .Arabic language affected many countries and the republics of Central Asia that are still written in the Arabic script to this day. The Divine Comedy is an Italian narrative poem written by Dante Alighieri is widely considered the pre-eminent work in Italian literature and one of the greatest works. The poem’s imaginative vision of the afterlife is representative of the medieval worldview as it existed in the Western Church .The researchers found a great similarities between the Divine Comedy and The Message of Forgiveness of Abu al-Ala al-Maari, the first to raise this controversy was the Spanish Orientalist priest Palatius 1919 in which he confirmed the effect of The Message of Forgiveness in comedy and supported by Arabic pens. Hence this study, tries to reveal what our Islamic literature has provided to the literature of West, and to clarify some aspects of the latter’s influence on it. It also aims to show the similarities between these two important works and show to what extent Dante’s work was influenced and taken from Islamic Literature